Recharging China in War and Revolution, 1882–1955 - Tan, Ying Jia (Cornell University Press, 2021)
"In Recharging China in War and Revolution, 1882–1955, Ying Jia Tan explores the fascinating politics of Chinese power consumption as electrical industries developed during seven decades of revolution and warfare.